Scalp infection by Candida Albicans in an immunocompetent patient: a description of a rare case. (4th July 2018) - Fortuna, Maria Caterina; Garelli, Valentina; Pranteda, Giulia; Carlesimo, Marta; D'Arino, Andrea; Rossi, Alfredo
Abstract : Candida is a large genus of yeast, consisting of about 150 species, among which C. albicans is the most prevalent fungal species of the human microbiota. C. albicans is the most important fungal opportunistic pathogen that can cause infection when the host becomes debilitated or immunocompromised. We report a case of a scalp infection by C. albicans in a patient without an obvious immunocompromised state.